A Triterpenoid Compound From The Leaves of Lantana camaraLinn. - Kartika MZ Kartika; Suryati Suryati; Mai Efdi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
A triterpenoid compound has been isolated from the ethyl acetate fraction of Lantana camaraLinn leaves. The isolation was performed by chromatography of gravitation column with a gradient elution system using hexane, ethyl acetate and methanol. Purification by recrystallization produces a white solid (20 mg) with a melting point of 288-289 °C. The results of elucidation of UV, IR, 1H-NMR, 13C-NMR, HMBC, HSQC, DEPT and COSY spectral data, it is known that the isolated triterpenoid compound is 22β-angeloyloxy-9-hydroxy-3-oxo-olean-12- en-28-oicacid with molecular formula C35H52O6. Keywords—Lantana camaraLinn, Chromatography of gravitation column, Triterpenoid, C35H52O6